Understanding Drivers behind Offenders Attacking European Religious Sites – Five Cases - Pethő-Kiss, Katalin (Perspectives on terrorism, 2022)
This Research Note presents an empirical examination of five violent extremist offenders who attacked European places of worship between 2010 and 2020. This focuses on both personal and socio-economic circumstances that may have been influencing these lone actors. First, the drivers and factors are organized in a matrix. Then the attackers are examined in the light of these matrix elements. Finally, based upon the findings, a number of recommendations are made.